HUBUNGAN PERSEPSI PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN USIA PADA MASYARAKAT YANG SUDAH PERNAH MELAKUKAN PERAWATAN DI KLINIK GIGI PUSKESMAS II TAMPAKSIRING TAHUN 2016 - I Made Budi Artawa; Ni Luh Made Yudari (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
Primary preventive measures to prevent oral and dental diseases can be carried out especially by individuals. Dental and oral hygiene measures can be done by individuals by brushing teeth. in addition to behavioral factors, there are also other factors that affect health is perception. A person's age and maturity can influence perception. The results of Ni Luh Made Yudari's research at Tampaksiring II Puskesmas dental clinic concluded that the people who visited and had already treated at the Tampaksiring II Puskesmas Dental Clinic had the most perceptions with good criteria. The purpose of this study was to determine the relationship between perceptions of dental and oral health maintenance with age in people who had already taken care at the Dental Clinic II Tampaksiring in 2016. The type of cross sectional study, used secondary data from Ni Luh Made Yudari research. Spearmen correlation test between the age variable and the perception variable, obtained sig .: 0.280. there was no relationship between the age variable and the perception variable in the community who had taken care at the Tampaksiring II Dental Clinic in 2016.